The Comfort of Strangers: on my Blueberry Nights - Duarte, José (2013)
‘How do you say goodbye to someone you can’t imagine living without?’ asks Elizabeth (Norah Jones) in voice-over before leaving the café in New York, run by Jeremy (Jude Law), to start her journey from east to west, throughout the American landscape. This is the basic plot of My Blueberry Nights (2007), the first full-length film in English directed by Wong Kar-wai, also known for his other films like Chungking Express (1994), In the Mood for Love (2000) or 2046 (2004). My Blueberry Nights is the story of a girl who goes soul-searching after discovering her boyfriend has left her for another woman. As the movie opens we are presented with an image of trains running back and forth, like the lives of the protagonists, particularly Elizabeth who will be going on a road trip to find herself.